PREDICTIVE VALUE OF INFLAMMATORY CYTOKINES IN PREDICTING THE RISK OF PROLIFERATIVE DIABETIC RETINOPATHY - Majidova, S.R. (World of Medicine and Biology, 2024)
A retrospective clinical and immunological study determined the diagnostic value of inflammatory cytokines in predicting the development of proliferative diabetic retinopathy. 82 patients with diabetes mellitus were divided into two groups: group 1 – 40 patients without developing proliferative complications of diabetic retinopathy and group 2 – 42 patients with the transition of non-proliferative diabetic retinopathy to proliferative one. In the blood of patients of the second group, there was a significantly higher level of concentration of the cytokines TNF-α (Pu=0.001), IL-1β (Pu
Keywords: diabetic retinopathy; tumor necrosis factor-α; interleukin-1ß; interleukin-8; interleukin-4; prognosis criteria; inflammation